Measuring pressure in different layers of the ski boot to estimate skiing movements - Hermann, A.; Carqueville, P.; Baldinger, M.; Senner, V. (Proceedings of the 9th International Conference on Sport Sciences Research and Technology Support icSPORTS - Volume 1, 2021)
A pressure sensing measurement ski boot or sock would allow to estimate body positions, skiing manoeuvres, and external loads on the foot. This information may be used for research, in consumer products or for intelligent safety systems like a mechatronic ski binding. To investigate the optimal placement of pressure sensors with respect to the foot and the number of sensors needed to detect six pre-defined loading conditions, three pressure sensor systems were developed measuring the pressure in three respective layers: between foot and sock, sock and liner, liner and shell. The prototypes were evaluated in a laboratory test. The participant performed a series of six simulated ski manoeuvres each held for 5 seconds. In this pilot test the system sock / liner shows the best overall performance due to pressure curves in the mid-range of the sensor characteristics. Though, with an optimized sensor design a measurement boot with sensors between inner boot and shell may be possible, which would increase the robustness of the system needed for a future customer product. As a result of this study, a recommendation for sensor positions for the determination of the loading conditions in alpine skiing is given.